Influence of drying on the insulation power factor of distribution transformer windings - Ramos Carrión, Jorge Carmelo (2018)
The present article exposes the development of the investigation on the analysis and determination of the influence of the process of elimination of the humidity, absorbed by the solid isolation of the windings, in the power factor of the isolation of the distribution transformers. Considering the power factor as a characteristic parameter that allows to determine how dry the insulation is and thus define its quality from the electrical point of view. It was shown that there is a significant influence on the power factor.